2009
DOI: 10.1007/s10482-009-9320-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA and Type IV pili mediate surface attachment by Acidovorax temperans

Abstract: Extracellular DNA can play a structural role in the microbial environment. Here evidence is presented that an environmental isolate of Acidovorax temperans utilises extracellular DNA for intercellular and cell-surface attachment and that Type IV pili and electrostatic interactions play a role in this interaction. Preliminary attempts to isolate and purify extracellular polysaccharides from A. temperans strain CB2 yielded significant amounts of DNA raising the question of whether this molecule was present as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In contrast, the significance of eDNA for cellular attachment and structural integrity has more recently been recognized for an increasing number of Gram-negative and Grampositive species (Whitchurch et al, 2002;Steinberger and Holden, 2005;Allesen-Holm et al, 2006;Moscoso et al, 2006;Jurcisek and Bakaletz, 2007;Qin et al, 2007;Izano et al, 2008;Thomas et al, 2008;Heijstra et al, 2009;Vilain et al, 2009;Harmsen et al, 2010;Lappann et al, 2010). Release of DNA in bacterial biofilms has mainly been attributed to the lysis of a cellular subpopulation, mediated by the activity of autolysis systems (Allesen-Holm et al, 2006;Rice et al, 2007;Thomas et al, 2008Thomas et al, , 2009Mann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the significance of eDNA for cellular attachment and structural integrity has more recently been recognized for an increasing number of Gram-negative and Grampositive species (Whitchurch et al, 2002;Steinberger and Holden, 2005;Allesen-Holm et al, 2006;Moscoso et al, 2006;Jurcisek and Bakaletz, 2007;Qin et al, 2007;Izano et al, 2008;Thomas et al, 2008;Heijstra et al, 2009;Vilain et al, 2009;Harmsen et al, 2010;Lappann et al, 2010). Release of DNA in bacterial biofilms has mainly been attributed to the lysis of a cellular subpopulation, mediated by the activity of autolysis systems (Allesen-Holm et al, 2006;Rice et al, 2007;Thomas et al, 2008Thomas et al, , 2009Mann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Acidovorax temperans is an abundant member of activated sludge. A. temperans strains CB2 is known to adhere readily to surfaces, where it forms biofilms [37]. …”
Section: Resultsmentioning
confidence: 99%
“…Our results show that the deletion of HipBA of E. coli BW25113 significantly reduced the biofilm biomass. eDNA is an important component of the biofilm matrix (Heijstra et al, 2009;Rice et al, 2007;Spoering & Gilmore, 2006). Recent studies have shown that bacterial programmed cell death has multiple functions, including releasing eDNA that could have a function in structuring biofilms (Rice et al, 2007;Webb et al, 2003;West et al, 2007).…”
Section: Discussionmentioning
confidence: 99%